KARAKTERISASI MEMBRAN KOMPOSIT KITOSAN-SILIKA HASIL SINTESIS UNTUK SEL BAHAN BAKAR - M. Ali Zulfikar, ; D. Wahyuningrum, ; S. Achmad, ; N. Tanyela Berghuis, (Matematika dan Sains, 2009)
The composite membrane of chitosan-silica in various curing temperature could be synthezed. It was synthezed using sol-gel method and reverse phase in various curing temperature. The resulted membrane was characterized its physicochemical properties including methanol permeability, ion exchange capacity, water absorbtion, structure by FTIR, ion conductance, morphology analysis using SEM. The results showed that methanol permeability and water absorbtion value decreased with increasing curing temperature, in the other hand ion exchange capacity and ion conductace increase. Morphology analysis result showed that the surface of membrane becomed lebih rapat with increasing curing temperature.